Pathophysiology : the biologic basis for disease in adults & children - McCance, Kathryn L; Huether, Sue E (Mosby, 2002)
As the leading pathophysiology textbook for over a decade, this outstanding resource boasts comprehensive coverage, complete and separate treatment of pediatric pathophysiology, a clear writing, and numerous full-color illustrations. In its new 4th edition, this authoritative classic features extensively revised and updated content, more illustrations, and a greatly enhanced full-color design. The first part presents the general principles of pathophysiology, including -- cellular structure, injury, and repair; fluids and electrolytes, and acid-base balance; immunity, inflammation, and infection; stress; and oncogenesis. It also discusses the influence of the environment and the role of genetics in the development of disease. The second part, organized by body system, examines normal anatomy and physiology, alterations of function in adults, and alterations of function in children.
Keywords: patologie; fyziologie; Nemoci dětské; Patofyziologie